Interest Rate Policy in the Republic of Macedonia - Zoran Stavreski (National Bank of the Republic of Macedonia, 1998)
The interest rate policy is one of the most significant economic policy instruments. Current evidence from developed countries, as well as from countries in transition, shows that the optimal interest rate policy is an essential precondition for achieving dynamic economic growth. Extremely low level of domestic saving in the banking system versus high and rigid demand for funds, high risk premiums due to the lack of financial discipline and inefficient juridical system, and high operational costs, determined interest rates in the Republic of Macedonia in the last two years to be formed on high nominal and real level. The long-run solution of the unfavorable situation in the field of interest rate policy necessarily means improvement of fundamental economic performances which determinate interest rate policy, and it is, first of all, the relation between supply and demand of resources, i.e. in the national identities the relation between saving and investment. However, in the short run, some measures can be undertaken which would have a positive influence on interest rate policy, and in the same time they would not disturb the main market principles, meaning banks independence in designing and implementing the interest rate policy. These measures are: 1. To revise the existing tax policy which has a negative influence on saving; 2. To increase the interest rate which the National Bank of the Republic of Macedonia pays to the banks on the compulsory reserves; 3. Designing and implementation of internal policies, procedures and standards by banks for credit approval, sound credit portfolio management and more efficient claims collection; 4. Strengthening of the supervision regulation concerning provisions for bad placements of the banks; 5. To improve the efficiency of the juridical system and instruments for protection and insurance of the claims (collateral); 6. To revise the existing law regulation concerning the Deposit Insurance Fund; 7. Acceleration of the activities for foundation of the credit register; 8. Adoption of the practice of "prime rate" formation; 9. Change of the operative procedures under the Law for foreign exchange operation; and 10. Stimulation of foreign capital inflow in the form of direct investments, by which the total supply of funds in the Republic of Macedonia will be increased.
Keywords: 330